Legal Protection for Businesses in Consumers of Electronic Goods - Kusumawardana, Muhammad Yudha (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2024)
The objective of this research is to assess how effectively Law No. 8 of 1999 on Consumer Protection is implemented in safeguarding consumers from the misconduct of business operators. Additionally, the study emphasizes the efforts made by consumers to secure their rights from these operators. The research aims to provide insights into how government actions can enhance consumer protection in the future. The research reveals that to protect consumers from deliberate fraud by business operators, the government has established a body for consumer protection and recognized non-governmental consumer protection organizations. Furthermore, to claim their rights, consumers often resort to both the formal court system and alternative dispute resolution methods. Looking ahead, it is suggested that the government should focus more on strengthening mechanisms to protect the rights and obligations of all economic actors (consumers, producers, and distributors).